2018
DOI: 10.1123/ijsnem.2017-0389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Versus Low Protein Intake on Body Composition and Maximal Strength in Aspiring Female Physique Athletes Engaging in an 8-Week Resistance Training Program

Abstract: Aspiring female physique athletes are often encouraged to ingest relatively high levels of dietary protein in conjunction with their resistance training programs. However, there is little to no research investigating higher versus lower protein intakes in this population. This study examined the influence of a high versus low-protein diet in conjunction with an 8-week resistance training program in this population. A total of 17 females (21.2 ± 2.1 years; 165.1 ± 5.1 cm; 61 ± 6.1 kg) were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…The combination of reduced MPS and increased MPB results in a negative net protein balance, which could be attenuated with high protein intakes. However, there are very few studies, observational or intervention-based, comparing high and low protein intake in athletes during a caloric deficit (Campbell et al, 2018;Helms et al, 2015;Longland et al, 2016;Walberg et al, 1988). For example, a recent study found that over a 4-week period, a 40% caloric deficit with 2.4 g/kg/day of protein per day resulted in more LBM preservation and more fat mass loss compared to a group consuming 1.2 g/kg/day (Longland et al, 2016).…”
Section: Macronutrient Intake Proteinmentioning
confidence: 99%
“…The combination of reduced MPS and increased MPB results in a negative net protein balance, which could be attenuated with high protein intakes. However, there are very few studies, observational or intervention-based, comparing high and low protein intake in athletes during a caloric deficit (Campbell et al, 2018;Helms et al, 2015;Longland et al, 2016;Walberg et al, 1988). For example, a recent study found that over a 4-week period, a 40% caloric deficit with 2.4 g/kg/day of protein per day resulted in more LBM preservation and more fat mass loss compared to a group consuming 1.2 g/kg/day (Longland et al, 2016).…”
Section: Macronutrient Intake Proteinmentioning
confidence: 99%
“…Body composition was assessed using the BodyMetrix™ BX-2000 A-mode ultrasound (IntelaMetrix, Livermore, CA, USA) with a standard 2.5 MHz probe according to procedures as previously described [14]. All body composition assessments were completed by the same two trained technicians.…”
Section: Body Composition Assessmentmentioning
confidence: 99%
“…There is a dearth of scientific inquiry into healthy, non-overweight individuals, who may be motivated to lose weight to improve physical appearance and enhance self-perception as opposed to health outcomes [11]. For this population, weight loss efforts aim to reduce fat mass while maintaining/gaining fat-free mass by implementing a caloric deficit with a relatively high dietary protein intake, a slow rate of weight loss, and engaging in a resistance training program [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Within the off-season phase, physique athletes manipulate resistance training variables including volume, intensity and frequency for the purpose of gaining LBM (Spendlove et al, 2015). This period can last years and is characterised by a positive energy balance, in conjunction with a high protein intake to stimulate muscle anabolism (Phillips, 2004;Campbell et al, 2018). In the pre-competition phase, the majority of athletes attempt to reduce body fat levels and preserve LBM using a combination of rigorous resistance and aerobic training, while manipulating their nutritional intake to achieve a negative energy balance (Hackett et al, 2013;Petrizzo et al, 2017).…”
Section: Body Composition In Competitionmentioning
confidence: 99%
“…Female physique (FP) athletes have aspirations of achieving a lean and muscular body composition for competitive success (Halliday et al, 2016). Preparing for a natural physique competition provides a myriad of health benefits including improvement in cardiovascular status (Kistler et al, 2014;Robinson et al, 2015), muscle strength (Campbell et al, 2018), increasing feelings of accomplishment, and transient improvements in self-esteem (Aspridis et al, 2014;Baghurst et al, 2014;Probert et al, 2007). Despite these positive outcomes, numerous unfavorable effects also exist, including, but not limited to: diminished levels of reproductive hormones (Hulmi et al, 2016) and symptoms of disordered eating and eating disorders (DE/ED) (Walberg and Johnston, 1991).…”
Section: Introductionmentioning
confidence: 99%